THE CONSTRUCTION OF MENS REA AND THE CRIMINALIZATION OF DISCRETION IN INDONESIA - Pardomuan Robinson Sihombing (Jurnal Suara Keadilan, 2026)
Law enforcement of corruption crimes in Indonesia faces a fundamental paradox between the demands of integrity and the need for public officials' discretionary flexibility. The phenomenon of "policy criminalization" has created profound legal ambiguity, blurring the boundaries between business risk, maladministration, and malicious intent (mens rea). This study aims to deconstruct the application of the doctrine of Business Judgment Rule (BJR) and analyze the psychological mechanisms of moral disengagement that underlie the behavior of public officials and the cognitive biases of Law enforcement officials. Using qualitative methods, this study examines four landmark cases: Karen Agustiawan (Pertamina), Dahlan Iskan (PT PWU), Tom Lembong (Sugar Import), and Ira Puspadewi (ASDP). The study's findings reveal extreme judicial inconsistencies. Although the Supreme Court once recognized the BJR (Karen 2020 & Dahlan 2019 cases), the recent trend of 2025 in the cases of Tom Lembong and Ira Puspadewi shows a return to the rigid positivistic approach that criminalizes policies without evidence of personal gain (kickback), which then triggers executive intervention through the granting of Abolition and Rehabilitation by the President. Compared with the standards of proof in Indonesia, the doctrine of Misconduct in Public Office in the United Kingdom or the Official Act in the United States is much stricter. This study recommends explicit codification of BJR and reform of mens rea proof that requires real psychological indicators of malicious intent.